Have Regulatory Efforts to Reduce Organophosphorus Insecticide Exposures Been Effective? - Clune, Alison L. (National Institute of Environmental Health Sciences, 2012)
Background: The Food Quality Protection Act (FQPA) was signed into law in 1996 to strengthen the regulation of pesticide tolerances in food. Organophosphorus (OP) insecticides were the first group of pesticides reviewed by the U.S. Environmental Protection Agency (EPA) under the new law. Objective: Our goal was to determine whether urinary concentrations of dialkylphosphate (DAP) metabolites of OP pesticides declined between the National Health and Nutrition Examination Survey (NHANES) III and NHANES 1999–2004. Methods: Using mass spectrometry–based methods, we analyzed urine samples from a nationally representative sample of 2,874 adults 20–59 years of age in NHANES 1999–2004 and samples from a non-nationally representative sample of 197 adult participants for NHANES III (1988–1994) for six common DAP metabolites of OP pesticides. Results: Median urinary DAP concentrations decreased by more than half between NHANES III and NHANES 2003–2004. Reductions of about 50%–90% were also observed for 95th percentile concentrations of five of the six metabolites. Frequencies of detection (FODs) decreased in all six metabolites (< 50% reduction). On average, median and 95th percentile concentrations and FODs showed a larger decrease in diethylphosphate metabolites than dimethylphosphate metabolites. Conclusions: Human exposure to OP insecticides as assessed by urinary DAP concentrations has decreased since the implementation of the FQPA, although we cannot be certain that U.S. EPA actions in response to the FQPA directly caused the decrease in DAP concentrations.